Resposta espectral da cultura do feijão e sua relação com parâmetros biofísicos em diferentes doses de nitrogênio - Chicati, Mônica Sacioto (2015)
Remote sensing has become an indispensable tool for the monitoring of agricultural production in Brazil, since his study assumes that each object has its spectral signature with a single behavior. Therefore, different objects interact differently with electromagnetic energy in some wavelengths, thereby allowing identification and determination. In modern agriculture, the use of methods that provide rapid diagnosis of the nutritional status of plants such as the identification of nutritional stress and production of components is a necessity for a recommendation of optimized fertilization. The aim of this study was to compare the diffuse spectroradiometric with digital images to discrimination of nitrogen in beans. The specific objectives were to propose vectors extracted vegetation indices digital images captured by a digital camera using different filters (IR 720nm, 850nm IR and UV-IR cut) compared with the rates obtained with the use of a spectroradiometer; evaluate the use of the indices alone in the setting of linear models for discrimination between nitrogen levels in the bean crop and its relation to the production of components, and to establish the spectral behavior of the bean crop at different levels of nitrogen applied during his development. The experiment was installed on Irrigation Training Centre (CTI) of the State University of Maringa (UEM). We used a completely randomized design (CRD) with five treatments (0, 60, 100, 200 and 300 kg ha-1 N) and 10 repetitions, with the cultivar IPR Tangara. The capture of images and readings were held periodically being established at 20, 27, 30, 33, 36 and 48DAE, (07/oct, 14/oct, 17/oct, 20/oct, 23/oct and 04/nov respectively) where the first five evaluations were made before flowering and the sixth review when 100% of the plants had already blossomed. The collected data were processed using the Spring and Excel software for calculation of GNDVI vegetation indices, NDVI, GNIR and RNIR. To 48DAE evaluated the leaf nitrogen content, leaf area, dry mass, chlorophyll and carotenoids. As a result, it was observed that the bean spectral behavior changes with different levels of nitrogen, especially in the visible region of the spectrum, being more evident after 36 and 48DAE and larger responses when applied low doses of N. After flowering, there was difference in spectral response in the near infrared region. The Vegetation Index showed the best determinção coefficient was in the GNDVI 720 nm filter (20DAE), and then the RNIR the filter 850 nm (30DAE). The vegetation indices showed positive correlations, and the best was GNIR 36DAE using the spectroradiometer. In viii 100% of cases, all vegetation indices showed significant values for correlations of biophysical parameters using the 720nm and 850nm filters, and also using the spectroradiometer.